Malignant pleural mesothelioma in western Glasgow 1980-6. Issue 6 (June 1989) - Hulks, G; Thomas, J S; Waclawski, E
Abstract : This study reviews all histologically proved cases of malignant pleural mesothelioma seen in the western district of Glasgow during 1980-6. Sixty eight cases were identified (three female) with an age range at presentation of 48-85 (mean 68.9) years. Asbestos exposure was identified in 54 (80%) of the patients, most of whom had been shipyard workers. Pain and dyspnoea were the most common presenting symptoms. Pleural effusion was found in 57 (84%) of the patients, in a ratio of 2.6 right:left. The median survival was only 30 weeks from the time of presentation. Prognosis was significantly better for those presenting with dyspnoea than for those with pain (median survival 44 v 22 weeks). Postmortem examination was performed in 40 cases and metastatic disease found in more than three quarters. There was no significant difference between the incidence of the various tumour cell types or any relation between cell type and survival or the incidence of metastatic disease. A substantial increase in cases of malignant pleural mesothelioma has been found in an area of already high incidence. The use of rigorous histological criteria to determine histological cell type has shown that this previously valued variable is of no discriminatory value with regard to disease activity or survival.